THE ADDITION MANGOSTEEN PERICARP MEAL AND VITAMIN E IN THE DIET ON DIGESTIVE ORGANS, ACCESSORY ORGANS, REPRODUCTIVE ORGANS, AND CARCASS OF LAYING HENS - Rita Mutia; Ridho Kurniawan Rusli; Komang Gede Wiryawan; Toto Toharmat; Jakaria Jakaria (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
This research aimed to study long-term addition natural herbal: mangosteen pericarp meal and non-herbal: vitamin E in the diet on digestive organs, accessory organs, reproductive organs, and carcass of laying hens. A total of 160 laying hens of Lohman strains (24-wk-old) the observation was conducted for 11 weeks. Designs used are a completely randomized design with four treatments and four replications (10 birds each). The treatments consisted of R0 (control diet), R1 (R0 + 1 g MPM/kg ration), R2 (R0 + 2 g MPM/kg ration) and R3 (R0 + 200 mg VE/kg ration). The variabel observation were digestive organs (percentage of crop, heart, gizzard, spleen, kidney, small intestine), accesory organs (percentage of liver and bile), reproductive organs, body weight and carcass of laying hens. The results showed that all of treatments (RO, R1, R2, and R3) did not affect (P>0.05) internal organs (percentage of crop, heart, gizzard, spleen, kidney, small intestine), accesory organs (percentage of liver and bile), reproductive organs, body weight and carcass of laying hens. In conclusion, long-term addition of mangosteen pericarp meal 1-2 g/kg ration and vitamin E 200 mg/kg in the diet no adversed effect on digestive organs, accesory organs, reproductive organs, body weight and carcass of laying hens.